How have LIS school curricula evolved over the past twenty years? - Chung, EunKyung; Schalk, Janet; Yoon, JungWon (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2022)
This study analyzed the Association for Library and Information Science Education (ALISE) statistical reports from 1997 to 2020. This study demonstrated that over the past twenty years, the LIS trends of diversity and interdisciplinary work have all been well reflected in the LIS curricula both in iSchools and non-iSchools, and LIS schools are preparing their graduates for evolving information environments.